Catalonia rescaling Spain: is it feasible to accommodate its “stateless citizenship”? - Calzada, I (Wiley, 2019)
The Spanish nation‐state is gradually being rescaled by Catalonia's “secession crisis.” Recently and dramatically, in the aftermath of the “illegal” and “constitutive referendum” that took place on 1 October 2017, 2,286,217 Catalan citizens attempted to exercise the “right to decide” to ultimately become “stateless citizens.” This paper examines this rescaling process that has been forming in Barcelona since 10 July 2010 when 1 million Catalan citizens marched to claim their “right to decide” on secession. This paper concludes that, at present, it is not feasible for the Spanish nation‐state to accommodate Catalonia's “stateless citizenship.”